Édito - Interroger l’hospitalité scolaire à l’aune d’une injonction au bien-être - Frédérique-Marie Prot (Recherches en Éducation)
Following on from a number of recent works, the aim of this issue of the journal is to re-examine, directly or indirectly, the concern for well-being that pervades our institutions, by confronting such concern with the need to understand what constitutes the principle of an emancipatory school education. If we take the school as a place of hospitality, its meaning presupposes the ethical dimension of the didactic relationship. But we also need to examine the material conditions of teaching and its pedagogical organisation as sources of unhappiness at school, for pupils and teachers alike, since the 19th century. This dossier is part of a series of research studies into what might be called the school « lifestyle ». Life at school, and in particular that of the pupils who spend a large part of their time there, was already at the heart of the concerns of the New Education movement. As Jean-François Dupeyron pointed out: « School is a place where pupils, accompanied by adults, learn to live by practising and learning through their experiences ». We need to look at this phrase learning to live: what experience does it cover? In recent years there has been a proliferation of surveys on the theme of « well-being at school ». Some studies even raise the question of « happiness at school », often from a personal development perspective and based on the doctrines of « humanist psychology » or « positive psychology ». The dossier we are proposing to produce takes a critical approach to the concrete reality of the educational institution to which children are entrusted.